Effects of water deficit on fruit quality and water productivity of citrus under plastic film mulching in Western Hubei, China - Zhong, Yun; Huang, Zhikun; Hao, Kun; Zhu, Shijiang; Fei, Liangjun; Zeng, Jian; Dai, Zhiguang; Wang, Yalin (Frontiers in Plant Science, 2025)
IntroductionThe cultivation of Citrus sinensis Osbeck, the fruit with the largest planting scale and yield in Western Hubei Province of China, currently faces significant challenges related to low fruit quality and water use efficiency (WUE). This study aims to enhance citrus quality, yield, and WUE in the region by investigating the effects of water deficit and film mulching on 10-year-old citrus trees.MethodsFrom 2019 to 2021, three levels of water deficit (Light: 80%-90%, Moderate:70%-80%, Severe: 60%-70% of field capacity) and four mulching treatments (A: Japanese film, B: Dupont film, C: Chinese film, and no mulching) were implemented at the young fruit stage. Full irrigation (90%-100% of field capacity) was used as the control.Results and discussionThe light reflectance of films A, B, and C increased by 43.7%, 44.6%, and 6.3% respectively on sunny days compared to no mulching. Films A and B exhibited 2.2 times higher reflectivity than film C. Moderate water deficit - Japanese film (M-A) and moderate water deficit - Dupont film(M-B) treatments demonstrated the greatest improvement in citrus quality. Water deficit combined with film mulching resulted in an average increase in WUE of 10.90%-20.35% compared to full irrigation, and 8.96%-16.52% compared to no mulching. Mulching led to an average increase in citrus yield of 3.09%-16.48% compared to no mulching. The interaction between water deficit and film mulching significantly influenced both yield and WUE. From 2019-2021, M-A and M-B treatments yielded the highest citrus production, consistently demonstrating superior performance. Therefore, the better treatments would be a combination of M-A and M-B treatments, which correspond to soil moisture levels of 70% θf–80% θf during the young fruit period of citrus under mulching with films A and B. This combination was expected to enhance citrus quality, yield, and WUE. The outcome of this study may offer scientific basis and technical support for citrus irrigation management in Western Hubei, China.